Work engagement, resilience and turnover intentions among nurses: a mediation analysis - Collins Atta Poku; Jonathan Bayuo; Veronica Adwoa Agyare; Nana Kobi Sarkodie; Victoria Bam (BMC Health Services Research)
Abstract Introduction Healthcare organizations experience difficult challenges as a result of nursing staff turnover. This is because it not only interrupts continuity of service but also its financial implications. Aim The purpose of the study was to find out the effects of work engagement on nurses' intentions to leave their jobs while considering resilience as a mediating factor. Methods The study used a descriptive-analytical design using a survey questionnaire on nurses working in different healthcare settings. The Utrecht Work Engagement Scale, the Brief Resilience Scale, and the Turnover Intention Scale were among the validated scales that were employed. The hypothesized relations were tested using descriptive and mediation analyses at a significance of <0.05. Results Though the turnover intention (n = 3.83 ± 1.42) and the level of work engagement (n = 4.03 ± 1.32) among nurses were high, their level of resilience of nurses was average (n = 2.48, SD: 0.63). Resilience had a negative association with turnover intention (β =  − 0.5699, p < .0001), and there was also a significant negative association between work engagement and turnover intentions among nurses with resilience mediating the relationship (β = -0.0367, p < .05). Conclusion Disengaged nurses are more likely to leave their jobs. Moreover, resilience acts as a mechanism through which work engagement influences turnover intentions. The study emphasizes the need to encourage work engagement among nurses to lessen intentions to leave the profession. Among factors that can improve work engagement and resilience to reduce turnover include conducting regular engagement assessments, fostering positive workplace cultures, employing flexible scheduling practices, and offering resources for personal and professional development.